Un cas d’école des imbrications populations, peuplement et territoires : la Nouvelle-Calédonie - Alexandra Monot (Bulletin de l’Association de Géographes Français)
In New Caledonia, a French archipelago situated in the Pacific Ocean and benefiting from a large autonomy, the population, which included natives and non-natives, is diverse depending on how long they have been settled in the territory. Non-natives, who have settled in successive waves since 1855 in the context of colonization and then of the 1960s nickel boom, can be divided between Caldoches, metropolitans and other minorities (especially Asians and Oceanians), despite widespread interbreeding. This diversity is reflected in the territory by a division between inalienable Kanak customary lands and lands transferable to other populations, and by the maintenance of a customary system which was institutionalized in 1999 with the establishment of a customary Senate. The Matignon-Oudinot agreements (1988) thus ratified a division of the archipelago between the Kanaks (Northern Province and the islands) and the Caldoches (Southern Province).